The relationship between life style and social status of “Family of Martyrs and sacrifices” and “ordinary families” in Ahwaz city - Maryam Brahman; azita zangene; akbar hashemi fard (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2018)
The purpose of this research is to investigate the relationship between life style and social status of Family of Martyrs and Martyrs terms and ordinary families in Ahwaz city. Way of life is one of the same concepts of lifestyle that is recognized through values and methods of consumption. The methodology of this research is a descriptive correlational study. The statistical population in this study is 24794 Family of Martyrs 12397 Family of Martyrs families of 12397 ordinary families. Sampling is done by probabilistic sampling method. According to the Cochran formula, the sample size is 387 people (families). A written questionnaire was used to collect data. For data analysis, Pearson correlation and regression analysis were used. After the study, it was found that the socio-economic base, body management, religious participation, and cultural capital, respectively, have the greatest role in the lifestyle. The life style of the control and saffron families in terms of social status does not have a significant difference with the lifestyle of ordinary families.